2022
DOI: 10.1155/2022/9704287
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Design Model of Urban Landscape Space Based on Optimized BP Neural Network

Abstract: Urban landscape space planning is an important application field of landscape ecology. With the continuous development of the field of architectural optimization, more and more optimization methods have sprung up, including various intelligent optimization algorithms. Such intelligent optimization algorithms usually rely on traditional building performance simulation methods to obtain building performance indicators for optimization in the optimization process. However, intelligent optimization algorithms gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…e clustering of variables affecting the sample function is generally referred to as variable Q-type cluster analysis, while the clustering of variables affecting the sample variables is referred to as function variable R-type cluster analysis [21].…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…e clustering of variables affecting the sample function is generally referred to as variable Q-type cluster analysis, while the clustering of variables affecting the sample variables is referred to as function variable R-type cluster analysis [21].…”
Section: 1mentioning
confidence: 99%
“…. ., 24; first, the whole sample data set is clustered on the A1 dimensional group using the clustering method to obtain three classes of K m,n PSO (1,4,7,10,13,16,19,22), (2, 5, 8, 11, 14, 17 20, 23), and (3,6,9,12,15,18,21,24), and then apply the same method to cluster (1,4,7,10,13,16,19,22) first in A2 dimension to obtain one class (1,4,7,10,13,16,19,22) and cluster (2,5,8,11,14,17,20,23) in A2 dimension to obtain two classes (2,5,8,11,14,17) and (20,23), and one class (3,…”
Section: Empirical Analysismentioning
confidence: 99%
“…Taking Morden as an example, they believe that the positioning of small towns needs to consider a variety of factors, such as regional advantages, mature characteristic industries and cultural and creative industries, and local policy guidance. e authors (Vukovi ć Predrag, Č Avlin Gordana, and Č Avlin Miroslav) in various works proposed that the success of both rural tourism town in the UK benefits from natural hot spring resources, location conditions, and convenient transportation [16][17][18][19]. When studying the STP theory, (Daan Francois Toerien) found that the cultural and tourism towns have achieved good benefits in the innovative use of local characteristic resources [23,24].…”
Section: Related Workmentioning
confidence: 99%
“…In the next decade, operation oriented, resource integration, and fine management will become a new model of cultural tourism real estate. erefore, from the future positioning, it can be seen that the cultural tourism town urgently needs to clarify its own positioning, so as to lay a good foundation for better tourism integration in the future [16].…”
Section: Introductionmentioning
confidence: 99%
“…Today, in a digital era, computer technology is widely used in various elds [14][15][16][17][18][19], including architecture and urban areas. Concepts are parametric architectural design [20,21], computational urban design [22,23], urban big data analysis [24,25], and smart city emerge [26] one after another.…”
Section: Introductionmentioning
confidence: 99%